Determinants and effects of mall excitement - Cai, Peiyun (2008)
This study aims to provide a better understanding of the shopping demographics in the area of mall determinants. This is done by investigating the relationship between five factors (tenant variety, mall environments, shopping involvement, cognitive crowding and affective crowding) on shoppers' excitement and desire-to-stay at the mall. In addition, this research seeks to further understand the influence of excitement, desire-to-stay and involvement on mall repatronage intentions. In addition, this research seeks to further understand the influence of excitement desire-to-stay and involvement on mall repatronage intentions.